Kidney Transplantation. - Veroux, Massimiliano (Bentham Science Publishers, 2012)
This e-book is an overview of recent advances in the realm of kidney transplantation. The volume discusses developments in surgical procedures while presenting a perspective on possibilities for kidney transplant research in the future. It serves as a valuable reference work for clinicians seeking updated information on both operative and post operative kidney transplant management strategies.